Chacun pour tous - Vianney Lebasque (2023)
Abstract: The French Comedy Chacun Pour Tous (2018) tells the story of the French national team of Basketball ID (“Intellectual Disabilities”) participating in the 2000 Sydney Summer Paralympics. National coach Martin is desperately looking for capable members for his team; to create a competitive squad, he recruits additional non-disabled amateur basketball players, with whom the team eventually competes in Sydney. The narration deals with the individual experiences of the disabled and non-disabled players during the tournament. The film is based on true events: At the Sydney Paralympics 2000, the Spanish Basketball ID team won a gold medal with ten non-disabled players. The fraud was discovered, and the medal had to be given to the second place, Russia. Details: The film opens with Martin, coach of France’s national basketball ID team, desperately trying to recruit players for his team in disabled facilities after some members have left the team. In order to stay competitive and to preserve the French association for Basketball ID, Martin, initially against the wishes of his co-coach Sami, makes a plan to compete in the Paralympics with non-disabled players. The two places an ad and recruit amateur basketball players Stan, Pippo, André, Malik, and Michel in a banlieue. The group meets Martin’s plans with initial suspicion but eventually agrees to the plot. The plan is not confided (for now) to the remaining disabled players, Yohan and Freddie, nor to the team psychologist, Julia, who is also Yohan’s sister. In secret, Martin trains the new team members not only in basketball skills but also in a pseudo-disabled habitus and he is, which is supposed to help the team pass background checks. The players acquire supposedly disabled behaviours and successfully pass the entrance exam. Parallel to these preparations, Martin’s private life is shown, which is marked by the care of his physically disabled daughter Alice. The team travels to Sydney, and the tournament begins. A gap between the disabled and non-disabled ...